Frequency regulation control strategy for PMSG wind‐power generation system with flywheel energy storage unit. Issue 8 (10th January 2017) - Yao, Jun; Yu, Mengting; Gao, Wenzhong; Zeng, Xin
Abstract : To enhance the frequency regulation capability of direct‐drive permanent magnet synchronous generator (PMSG)‐based wind‐power generation system, the frequency regulation control strategy for wind‐power system with flywheel energy storage unit (FESU) based on fuzzy proportional plus differential (PD) controller is proposed in this study. According to the mathematical model of PMSG‐based wind‐power generation system with FESU, the small‐signal model of the whole system is deduced in detail. In addition, the eigenvalue loci of the system are investigated to obtain the appropriate ranges of FESU's PD controller parameters for ensuring the system stable operation. Meanwhile, the impact of system equivalent inertia and damping on system frequency stability is analysed. Furthermore, a fuzzy PD controller of FESU is designed to dynamically regulate the system equivalent inertia and damping, leading to improved grid frequency characteristics. Finally, simulation studies on a 2 MW PMSG‐based wind‐power generation system with 400 kW FESU verify the validity of the proposed control strategy, contributing to enhance the frequency stability of power grid.